The impact of travel constraints on travel intention among tourists in a destination: a case study of Mizoram / Rajdeep Deb, Himanshu Bhusan Rout and Reemina Narzary - Deb, Rajdeep; Bhusan Rout, Himanshu; Narzary, Reemina (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2024)
Over the years, the tourism and hospitality industry in Mizoram has been fairly affected by the perceived travel constraints. Though showing interests, many tourists are too reluctant to travel. Therefore, comprehending how travel constraints influence tourists’ travel intention to Mizoram is pivotal for enhancing the attractiveness of Mizoram as a potential tourist destination. The current study sought to examine the relationship between travel constraints and travel intention of individuals having no prior experience of travelling to Mizoram. The study identified four underlying travel constraints namely interpersonal travel constraints, structural travel constraints, intrapersonal travel constraints, and unfamiliar cultural constraints from the literature and pursued them in the context of Mizoram. Drawing upon 201 respondents, this study concludes that all the travel constraints influence tourists’ travel intention to Mizoram negatively and significantly. Among these constraints, structural travel constraints seem to be the constraints with strongest impact on the travel intention. Relatively limited research has tried to address the relationship between travel constraints and intention to travel. Also, this study is first of its kind offering empirical support showing how travel constraints impact tourists’ travel intention to Mizoram.